A Self-Powered Density-Based Device for Automatic Mixed-Oil Cutting in Field Pipelines - Zhen Zhang; Yonggang Zuo; Huishu Liu; Biao He (Sensors)
Efficient oil transportation in field-deployed mobile pipelines is critical, but mixed-oil zones at interfaces reduce quality and increase waste, necessitating effective interface detection and cutting. Existing online densitometers, such as vibrating tube or high-accuracy magnetic suspension types, typically require external power, limiting their use in remote or emergency/temporary field operations. A self-powered device is presented that leverages gravitational force variations acting on a float to detect density changes and trigger automatic cutting. Validated with gasoline, diesel, kerosene, and water, it achieves a 10 kg/<semantics>m3</semantics> resolution, deemed sufficient for functional batch separation in its target application, with switching times of 61–395 s for density differences (760–835 kg/<semantics>m3</semantics>). It supports 20–90% blending ratios, with a vent mitigating gas effects. The modular, robust, self-powered design suits emergency operations, offering a practical alternative to powered systems. Future work targets improved resolution and environmental testing.